(untitled) (Revista Argentina de Musicología, 2001)
A perusal of some works on musical ethnography before the l9th century shows that some of the concepts, attitudes and recurrent approaches of our discipline were hatched centuries ago and the fact that they are still around leads to the conclusion that they are more than just antecedents of the ethnomusicology thought. The traces of centuries old thoughts in recent papers does not hinder the formulation of ideas strongly motivated by the current demands of intercultural studies and the development of a growing sensitivity towards the need to dismantle asymmetric relations. Beyond all the differences between diverse ethnomusicology models - differing but equally valid - there is an increasing implicit adherence to all forms of dialogue intrinsic to works based on ethnography. A growing allocation of space to the native voices, an awareness of the continua! construction and re-construction of the discourses and narratives together with the questioning of monolithic paradigms and binary oppositions of categories characterize the present ethnomusicology ideas. Intuition and alternative ways of telling the tale demand their wightful place in the scientific writings. Through their deep and total commitment during their field experiences, scholars have become acutely aware that they are part of a renovated ethnomusicology project, something that al so allows them the use of new tools to interpret the meaning of the contributions of late scholars to the hi story of the discipline.